Modeling of the grain-shell mixture in a castor-cleaning machine (Ricinus communis L.) - Cruz Meza, Pedro; López Canteñs, Gilberto de Jesús; García Silva, Samuel; Márquez Rosano, Conrado; Romanchik Kriuchkova, Eugenio; Reséndiz Cantera, Omar (Revista Mexicana de Ciencias Agrícolas, 2018)
Currently the cleaning of the grains by means of vacuum is spreading, in the development of agricultural equipment, due to the absence of dust in the work area. A common problem is the accumulation of material in conflicting sectors of the cleaning system, such as in places of sudden changes of direction or section in the tubes. In particular, it is of special interest, the component that distributes the flow, since a correct design must ensure a homogeneous distribution of the flow of air and material, without clogging (accumulations). The objective of this work is to analyze the behavior of the grains and shells of the castor oil plant (Ricinus communis L.) in the cleaning system by means of the computational fluid dynamics (CFD) technique and the trajectory of the particle at the exit of the fan, to determine the proper minimum speed. In the simulation, the k-epsilon and DPM (discrete phase model) models of ANSYS FLUENT were used. A test bench and a metal structure was constructed and instrumented to compare the experimental and computational results. The comparison of the results showed a good qualitative and quantitative agreement (R2= 82%) in the velocity profile. The average speed was 5.98 and 5.09 ms-1 for the estimated and experimental respectively. The standard deviation was 1.85 and 1.63 ms-1 for the estimated and experimental speed respectively. Finally, the model of the trajectory of the particle adequately predicts the distribution of the material at the outlet of the ventilator.
Keywords: CFD; grain cleaning; trajectory